The sin(π/2-x) formula is given as follows:

sin(π/2-x)=cosx **…(∗)**

The formula of sin(pi/2-θ) is given by sin(π/2-θ)=cosθ. In this post, we will learn how to compute sin(pi/2-x) or sin(θ-pi/2).

## Proof of sin(pi/2-x) Formula

To establish the above formula **(∗)**, that is, the formula of sin(π/2-x), we need to apply the below formula:

sin(a-b) = sina cosb – cosa sinb **…( ∗∗)**

Put a=π/2, b=x. Thus, we get that

sin(π/2-x) = sin(π/2) cosx – cos(π/2) sinx

= 1⋅cosx – 0⋅sinx as we know that sin(π/2)=1 and cos(π/2)=0.

= cosx – 0

= cosx

So we have proved the formula of sin(π/2-x) which is given below:

sin(π/2-x) = cosx |

In the above formula, if we replace x by θ, we will get the formula of sin(π/2-θ) which is provided below:

sin(π/2-θ) = cosθ |

## Proof of sin(x-pi/2) Formula

In the above formula **(∗)** of sin(a-b), we put

a=x, b=π/2.

Thus, sin(x-π/2)

= sinx cos(π/2) – cosx sin(π/2)

= sinx ⋅ 0 – cosx ⋅ 1

= -cosx

So the formula of sin(x-π/2) is equal to sin(x-π/2)=-cosx.

Similarly, the formula of sin(theta-π/2) is equal to sin(θ-π/2)=-cosθ.

**Also Read:**

## FAQs

**Q1: What is the Formula of sin(π/2-x)?**

Answer: The formula of sin(π/2-x) is given by sin(π/2-x)=cosx.

**Q2: What is the Formula of sin(x-π/2)?**

Answer: The formula of sin(x-π/2) is given by sin(x-π/2)=-cosx.